2021
DOI: 10.3389/fvets.2021.725841
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic, Clinical, and Myeloid Marker Responses to Acepromazine Sedation in Arabian Camels

Abstract: Sedatives and tranquilizers are important in the control of excited camels during camel transport. This study was conducted to investigate the clinical sedation of camels with acepromazine and its correlation with pharmacokinetics and pharmacodynamics. The sedation score, heart rate, respiration, body temperature, and pharmacokinetics were monitored before and after acepromazine injection, and myeloid marker expression was analyzed using membrane immunofluorescence and flow cytometry. The distribution (t1/2α) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…[3][4][5] Meanwhile, a case report showed that ACP overdose resulted in several effects on the human central nervous system and cardiovascular toxicity, as well as causing conditions including central nervous system depression, respiratory depression, and hypotension, which are similar to other phenothiazines. [6][7][8] According to the Food and Drug Administration (FDA), acepromazine is only approved for use in animals such as dogs (0.25-0.5 mg per lb of body weight), cats (0.5-1 mg per lb of body weight), and horses (2-4 mg/100 lb of body weight), and the dosage can be given intravenously, intramuscularly or subcutaneously. 9,10 The illicit use of ACP, such as drug-facilitated sexual assaults, has been reported in the literature 2 due to the difficulty in detecting this drug since it is metabolized rapidly and extensively in the body.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Meanwhile, a case report showed that ACP overdose resulted in several effects on the human central nervous system and cardiovascular toxicity, as well as causing conditions including central nervous system depression, respiratory depression, and hypotension, which are similar to other phenothiazines. [6][7][8] According to the Food and Drug Administration (FDA), acepromazine is only approved for use in animals such as dogs (0.25-0.5 mg per lb of body weight), cats (0.5-1 mg per lb of body weight), and horses (2-4 mg/100 lb of body weight), and the dosage can be given intravenously, intramuscularly or subcutaneously. 9,10 The illicit use of ACP, such as drug-facilitated sexual assaults, has been reported in the literature 2 due to the difficulty in detecting this drug since it is metabolized rapidly and extensively in the body.…”
Section: Introductionmentioning
confidence: 99%